2019
DOI: 10.5424/sjar/2019171-12599
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytokine response of Escherichia coli lipopolysaccharide stimulated peripheral blood mononuclear cells in crossbred cattle, Tharparkar cattle and Murrah buffalo - An in vitro study

Abstract: Mastitis is a complex disease responsible for huge economic losses to the dairy sector. The causal organisms include a wide variety of micro-organisms including several species of bacteria. Escherichia coli has been identified as one of the most common gram-negative bacteria causing clinical mastitis in cattle. The immune system, of different species and/or breeds, tries to combat these pathogens in an inconsistent manner with differential mode and intensity of immune response, eventually producing contradicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Also researchers have demonstrated that sub-inhibitory concentrations of enrofloxacin (0.0125 mg/ml) were able to induce biofilm formation in in vitro in the E.coli isolated from bovine mastitis (Costa et al, 2012). Considering the results of the current investigation and the reviewed data of the various researchers across the globe, the difference in the incidence rates of bovine mastitis caused by E. coli in Jersey and HF cross breeds and graded Murrah buffaloes may be due to variation in the geographical location, size of sampling, macro and micro environment in which the animal resides, size of sampling, sanitary condition of udder, immune status of the animal, cell mediated immune response of the individual breed to E.coli infection (Sadashiva and Kaliwal, 2013, Shopsin et al, 2000and Sulabh et al, 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Also researchers have demonstrated that sub-inhibitory concentrations of enrofloxacin (0.0125 mg/ml) were able to induce biofilm formation in in vitro in the E.coli isolated from bovine mastitis (Costa et al, 2012). Considering the results of the current investigation and the reviewed data of the various researchers across the globe, the difference in the incidence rates of bovine mastitis caused by E. coli in Jersey and HF cross breeds and graded Murrah buffaloes may be due to variation in the geographical location, size of sampling, macro and micro environment in which the animal resides, size of sampling, sanitary condition of udder, immune status of the animal, cell mediated immune response of the individual breed to E.coli infection (Sadashiva and Kaliwal, 2013, Shopsin et al, 2000and Sulabh et al, 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Endotoxin tolerance can be induced by TLR ligands other than LPS and it had been reported to induce endotoxin that may underlie the ability of TRL ligands to augment cellular antimicrobial functions is metabolic reprograming which rapidly change to support specific innate immune cell needs. Macrophages and dendritic cells are known to shift their metabolic profile to one that glycolytic process over oxidative metabolism (Sumanta et al, 2009;Surabh et al, 2019) -Similar letters in one column indicate that there were no significant differences between the treatment and control groups at p > 0.05 -Different letters in one column that there were no significant differences between the treatment and control groups at p > 0.05 CONCLUION All Gram-negative bacteria have the most important structure in their cell wall, which is the LPS, which consists of three main parts which are O antigen, core oligosaccharide and lipid A. The LPS stimulate the immune system and produce many cytokines that have been studied (TNF-α and IL-6) where it was estimated after simulating it inside the animal bodies under studies with different concentrations of LPS where their level were differed, thus, concentrations of bacterial LPS can be injected with counted doses as a vaccine against many bacterial diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Así, la evaluación en células mononucleares de sangre periférica (PBMC), es un método que ofrece ventajas para la evaluación de la inmunocompetencia o el estado de respuesta específica (Friberg et al, 1994;Whiteside, 1994). Este método ha sido utilizado en la evaluación de la respuesta inmune en camellos y alpacas, tanto para la evaluación de la respuesta inmune frente a inmunógenos bacterianos o proteínas simples como para la evaluación de vacunas (More et al, 2013;Tambillo et al, 2014;Watanabe et al, 2014;Sulabh et al, 2019). En bovinos, utilizando la misma metodología se ha evaluado la capacidad de resistencia y/o susceptibilidad a enfermedades de algunas razas (Sulabh et al, 2019).…”
Section: Discussionunclassified